Black phosphorus nanodot incorporated tin oxide hollow-spherical heterojunction for enhanced properties of room-temperature gas sensors. Issue 5 (1st March 2023) - Liu, Jianqiao; Zhang, Chenyang; Wang, Yusheng; Chen, Xincheng; Jing, Ran; Song, Tianzi; Zhang, Zhe; Wang, Hu; Fu, Ce; Wang, Junsheng; Zhang, Qianru
Abstract: The marriage of traditional gas-sensing semiconductors with low dimensional nanostructures is expected to exhibit interesting properties in the detection of hazardous gases. Herein, novel hollow-spherical heterojunctions are assembled for thin film gas sensors by using p-type black phosphorus (BP) and n-type tin oxide (SnO2 ). Green synthesis strategies are employed to prepare BP nanodots and SnO2 quantum dots. The aerosol-assisted chemical vapor deposition is used to prepare thin films with hollow-spherical heterojunctions. The BP incorporation significantly improves the gas-sensing properties of SnO2 -based thin films, which demonstrate excellent response and repeatability to H2 S at room temperature. The BP-SnO2 heterojunction demonstrates more than twice the response and sensitivity of pristine SnO2 thin film. Moreover, the recovery ability is significantly improved and LOD is decreased to 50 ppb. The hollow-spherical heterojunction has a joint gas-sensing mechanism contributed by both of SnO2 and BP. The SnO2 provides fundamental receptor function for gas detection while incorporated BP facilitates the adsorption of target H2 S and provides additional electrons through the p-n junction tunnel. In addition, a slight negative dependence on humidity is observed for the gas sensor. It is ascribed to the competitive adsorption of water molecules on the BP-SnO2 heterojunction surface against H2 S molecules and chemisorbed oxygen. This work not only proposes novel heterojunction nanostructures for room-temperature gas detection, but also contributes to the functional integration of traditional gas-sensitive materials and emerging 2D materials in sensor technology.